Meningkatkan Keterlibatan Dan Hasil Belajar Peserta Didik Melalui Active Learning Berbantuan Quizizz Dengan TaRL - Faozan; Ilham Ari Elbaith Zaeni; Ronny Afrian (STAIN Bengkalis, 2025)
This study was conducted with the aim of optimizing academic achievement and enhancing the active engagement of Grade VII-E students at a public junior high school in Malang City through the implementation of an active learning model assisted by Quizizz, integrated with the Teaching at the right level (TaRL) approach. The research employed a Classroom Action Research (CAR) design carried out in two cycles. Data were collected through learning outcome tests (pre-test and post-test), engagement observation sheets, and perception questionnaires. Quantitative data analysis using paired t-tests showed a statistically significant improvement in learning outcomes (p < 0.05) following the intervention. Descriptive analysis of qualitative data also revealed an increase in student engagement, as reflected in active participation in discussions, enthusiasm in completing Quizizz quizzes, and interaction during lessons. Adjustments made between cycles—such as adapting questions based on TaRL and optimizing Quizizz gamification—contributed to the effectiveness of the method. It is concluded that the integration of active learning assisted by Quizizz and the TaRL approach positively influences students' academic performance and engagement, and represents an innovative strategy in technology-enhanced learning.